An exploration of the priority remote health personnel give to the development of the Indigenous Health Worker oral health role and why: Unexpected findings. (11th October 2013) - Walker, David; Tennant, Marc; Short, Stephanie D.
Abstract Objective This research was undertaken to explore the priority given by remote area health personnel to the development of the oral health role of Indigenous Health Workers and the rationale for this prioritisation. Design Semistructured individual interviews and focus group interviews were undertaken with remote area health personnel working alongside Indigenous Health Workers. Setting Three Indigenous community clinics and two regional centres of remote northern Australia. Participants Interviews were conducted with 32 remote health personnel (11 dental, 14 nursing, 5 medical and 2 allied health personnel). Results The findings highlight the strong support found among remote health personnel for the development of the Indigenous Health Worker oral health role emphasising not only the perceived high impact of oral disease on the health of community members and community health resources, but also on the clinical practice of remote health personnel. Conclusion In identifying the high priority given to the development of this role, the study has also highlighted the impact of oral disease on the practice of remote health personnel and the need to develop training for remote health personnel to respond to oral disease.